Humidity conditions of brick enclosures heat-insulated by polystyrene foam from various manufacturers - Myskin Sergei; Koroleva Tamara; Ivachev Mikhail (E3S Web of Conferences, 2023)
The most appropriate way to select materials for a heat-insulating coating of an exterior wall depends on the opportunity to prevent water condensate to appear in this enclosure and, during the development of design and detail documentation, to prevent harmful effects on the building structures (damages of enclosing structures, improved heat conductivity of materials and heat leaks from premises resulting in reduced energy efficiency of buildings) during operation. The analytical study has been conducted for the most efficient grades of heat insulators made of polystyrene foam for the bearing layer of a wall made of silicate bricks. Two options for heat-insulating layer materials are investigated: A) polystyrene foam by Radoslav, Pereslavl-Zalessky, plate No. 18; B) polystyrene foam by BASF, model Styropor PS 15. Based on the characteristics of the heat insulators selected for the study, the calculation and analytical method was used to determine probability of water condensate to appear in the wall structure at the exterior temperatures of –9.9 °С to –27 °С. The findings showed that when any heat insulators selected for the study is used as a heat-insulating layer, the bearing structure excludes condensate formation and strength characteristics of the enclosure will not be reduced due to the brickwork freezing.